Measurement of sustainability in beef cattle: challenges for responsible consumption and production of the 2030 Agenda (Research, Society and Development, 2022)
The production systems of beef cattle are facing complex global challenges. One of them refers to meeting the Sustainable Development Goals, which encourages systems to adapt to sustainable production standards proposed by science, consumers and other stakeholders. In this context, the objective of this article is to identify in the literature a set of indicators that contribute to achieving sustainability in the beef cattle production system. To achieve this proposal, it was decided to carry out an integrative literature review. The results showed the existence of performance indicators, indicators related to animals, as well as other structural and economic ones. However, no indicators were identified aimed at contributing to the achievement of sustainability of specific production systems of beef cattle. The relevance of this study is due to the recognition of a methodological gap, which represents a relevant measure to face the increasing challenges identified in global production systems. This information provides strategies that support the progress of relevant assessments and analyzes to address issues involved in the development of more sustainable day-to-day practices and more effective public policies. In addition, it contributes to meeting the dimensions of sustainability, within the scope of food production from animal protein.